Delivery of some Trapped Metal Elements in the Boron Nitride Nanocone: Application of Bio-Sensors in Cell Membrane using a DFT Evaluation - (:unkn) unknown (AMG Transcend Association, 2023)
Positive stranded In this article, it has been investigated the density functional theory (DFT) study on single metal atoms of Li, Na, K, Be, Mg, and Ca trapped in B9N9 and B40N40 nanocones as biosensors in our body. Boron nitride (BN) is one of the structures similar to different crystals of carbon. Those B–N bonds will be replaced in these structures instead of C–C bonds in carbon nanotubes. In this investigation, it has been accomplished the B3LYP// EPRII, EPRIII/ 6-311+G(d,p)/ lanl2dz to estimate the susceptibility of B9N9 and B40N40 nanocones for trapping metal atoms of Li, Na, K, Be, Mg, Ca through charge transfer, NQR, NMR, spectroscopy and HOMO-LUMO molecular orbital analysis. Finally, the obtained results have approved that B40LiN40, B40NaN40, B40KN40, B40BeN40, B40MgN40, and B40CaN40 with good resistance and the electrical conductivity can be applied as biosensors in transferring and releasing the metal atoms in the human body. These results could be generalized to other BnNn nanocones and may help their rational design for biosensors that conduct the reactions in the biocells.